Women health providers: materials on cures, remedies and sexuality in inquisitorial processes (15th–18th century) - Espina-Jerez, Blanca; Siles-González, José; Solano-Ruiz, M. Carmen; Gómez-Cantarino, Sagrario (Frontiers in Psychology, 2023)
Background: The first inquisitorial trials were against Muslims and Jews. Later, they focused on women, especially caregivers. Progressively, they were linked to witchcraft and sorcery because of their great care, generational and empirical knowledge. The historiography of health in the 15th-18th centuries still has important bibliographical and interpretative gaps in the care provided by women. Objective: to analyse the care provided by healers as health providers, accused by the Inquisition, justifying the importance of nursing in the diversity of community care in the 15th-18th centuries. Method: A scoping review was conducted following the Dialectical Structural Model of Care (DSMC). A database search was conducted for the period 2013-2022. Bibliographic and legislative resources were used. Cases and convictions from Castilla la Nueva were found in the National Historical Archive and the Diocesan Archive of Cuenca. Results: The concepts of healer, witch and sorceress envolved during the study period. They reflect and reveal the collective imaginary of the social structure. They had healing laboratories, practised psychological and sexual care. They used to accompany their therapeutic action with prayers and amulets. They shared their professional activity with their main denouncers, doctors, apothecaries and priests. They were usually women in socially vulnerable situations, who did not conform to social stereotypes. Conclusions: They were predecessors of today's nursing, they overcame socio-cultural difficulties, although they were condemned for it. Healers did not manage to regulate their profession, but they acted as agents of health in a society that demanded them while participating in the "witch-hunt".